Studies in Contemporary Jewry, Volume IX : Volume IX: Modern Jews and Their Musical Agendas. - Mendelsohn, Ezra (Oxford University Press, 1993)
The essays contained in this yearbook examine the place of music in the process of Jewish assimilation into modern Europe, the role assigned to music in forging a new Jewish-Israel national identity, and the role of music in preserving a traditional Jewish lifestyle.